Facets of shame and their impact on quality of life in patients with atopic dermatitis and psoriasis - Carsten Spitzer; Laura Lübke; Clara Wülfing; Katharina Meier; Georgios Kokolakis; Dennis Niebel; Caroline Mann; Ante Karoglan; Steffen Emmert; Alexander Thiem (Scientific Reports)
Abstract Shame is a complex emotion with different facets. Skin shame is a specific aspect of body shame, which involves the skin perceived as inferior or flawed. Its role in atopic dermatitis (AD) and psoriasis is not well investigated. This explorative study pursued three objectives: First, the comparative analysis of shame and its facets in AD and psoriasis. Second, analysis of the association of skin shame with other shame facets, depression, and anxiety. Third, exploration of the unique impact of shame and its different facets on quality of life (QoL) in AD and psoriasis patients. This cross-sectional online survey encompassing German-speaking patients included several self-report measures on skin and general shame, depression, and anxiety as well as the Dermatology Life Quality Index (DLQI), Patient-Oriented Eczema Measure (POEM), and Psoriasis Symptoms and Signs Diary (PSSD). Data from 413 adult participants with AD (N = 162) or psoriasis (N = 251) were analyzed. There were no significant differences in skin or general shame, depression, or anxiety between those with AD or psoriasis. Skin shame as well as other aspects of shame were associated with younger age, female sex, depression, anxiety, and QoL. Analysis of AD and psoriasis subsamples revealed significant correlations of disease severity with skin shame, depression, anxiety, and DLQI. Hierarchical linear regression analyses indicated that skin shame was the second most important determinant of QoL after self-assessed disease severity. Systematic consideration of shame in AD and psoriasis is necessary in order to effectively reduce disease burden and enhance QoL.